Critical success factor of information management and governance: A case from 2014 flood in Kemaman, Terengganu - Saad M.F.M.; Latif A.A.; Othman M. (Association for Computing Machinery, 2023)
Enterprise resource planning; Flood control; Information management; Zoning; Critical success factor; Field studies; Fixed Regulation Operation; Flood management; Malaysia; Standard operating procedures; Floods